A 28 year old woman with ventricular tachycardia and an abnormal chest radiograph. Issue 6 (1st June 2003) - Heath, M; Deubner, H; Stern, E J; Cooke, J E; Gill, E A
Abstract : A 28 year old white woman with no medical history presented to the emergency room with symptomatic non-sustained ventricular tachycardia. She was asymptomatic up to a few days before presentation. Her physical examination was essentially normal and hence did not help with the differential diagnosis of the problem. Bronchoscopic transbronchial biopsy led to the final diagnosis of cardiac sarcoidosis.